Development and Validation of an Attributional Style Questionnaire for Adolescents. - Rodríguez-Naranjo, María Carmen; Caño-González, Antonio (American Psychological Association, 2010)
We describe the development and psychometric characteristics of a new version of the Attributional Style Questionnaire (ASQ; Seligman, Abramson, Semmell, & Von Baeyer, 1979)—a version called the Attributional Style Questionnaire for Adolescents (ASQ-A)—using 3 samples (Ns 547, 438, and 240) of Spanish secondary school students. In Study 1, the initial pool of 87 items was reduced to 54. Study 2 further analyzed the 54 scale items and revealed that the Internality, Stability, and Globality subscale scores had good reliability, good factorial construct validity, and satisfactory associations with maladaptive mood ratings. In Study 3, the regression analyses showed good and specific predictive validities of ASQ-A subscales for the attributions that the adolescents made about a particular real-life stressful situation. Study 4 showed that over an 8-month period the changes in the Stability and Globality subscales depended on the intensity of stressful life events experienced in this period. Overall, the studies revealed that the new ASQ-A served as an appropriate instrument to assess attributional style in adolescents.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/3503 (Accepted Version [pathway a])
Keywords: Estrés (Psicología); Adolescentes - Psicología; Attributional Style Questionnaire for Adolescents; Psychometric properties; Predictive validity; Sensitivity to stressful life events